Hydrodynamics and hydrographic patterns of the Gulf of Suez - Rocha, Filipa Morbey Ferro (2020)
The Gulf of Suez is a very rich area of coral reefs and tourism having great social and scientific interest to study the different parameters that influence this ecosystem. The objective of this work is to evaluate the influence of tides, to study local variations of salinity and temperature of water, to calculate tidal amplitudes, to characterize their hydrodynamics and to study the local regime of tides. The hydrodynamic model, Delft3D-Flow, was implemented, calibrated and validated by Eladawy et al. (2018), and was used in this study. The results show that the tide is of microtidal type, with amplitudes in the order of centimeters. The most important harmonic constituents in this ecosystem are the semidiurnal constituents. Local surface hydrodynamics are strongly influenced by wind patterns, essentially north-northwest, and salinity and temperature variations. In summary, the numerical model used proved to be a crucial tool for the hydrographic and hydrodynamic characterization of the Gulf of Suez.